A robust multi-objective joint scheduling of integrated electricity and gas grids considering high penetration of wind and solar units and flexible loads towards achieving a sustainable operation - Tabar, Vahid Sohrabi; Jirdehi, Mehdi Ahmadi; Jordehi, Ahmad Rezaee (International journal of hydrogen energy, 2023)
The cooperative planning of interconnected networks to achieve a sustainable operation and satisfy the welfare of all agents has become a critical issue. This paper optimizes the joint scheduling of integrated electricity and gas grids composed of wind turbines, photovoltaics, storage systems, power to gas and gas to power units. In this regard, a risk-constrained multi-objective programming is suggested to simultaneously model the operation costs of both networks and a robust augmented epsilon constraint method is applied to solve the problem and obtain the Pareto set. In order to simulate realistic conditions, uncertainties of wind and solar energies, electrical and gas loads and energy and gas prices are also considered. As well, the impact of flexible electrical and gas loads is analyzed using a time-of-use demand response program. According to the simulations, the presented approach is capable to create a good equilibrium between both networks. The results validate that the risk-averse strategy significantly increases the costs of electrical and gas grids by 21.41% and 10.36% compared to the risk-neutral strategy, respectively. In return, the robustness is improved against fluctuations caused by uncertain parameters. Moreover, responsive loads enhance decision flexibility and decrease the mentioned costs by 2.26% and 7.83%, respectively. •Joint scheduling of electricity and gas grids by multi-objective programming.•Deploying power to gas and gas to power technologies and storage systems.•Introducing a robust augmented epsilon constraint algorithm for optimization.•Modeling the uncertainty of renewable energies, electrical/gas loads and markets.•Implementing a time-of-use demand response program for electrical and gas loads.